On efficient data distribution in multipath TCP. (2017) - Yadav, Ram Narayan; Sharma, Kapil
Nowadays, internet devices are becoming multi-homed. To utilise the multiple links, it is needed to use all the interfaces for transmission. Multipath TCP (MPTCP) is an effort that enables end points to distribute data over interfaces simultaneously. However, alternatively distributing data over links cannot utilise the network resources. Due to different characteristics of subflows, out-of-order data arrived at the receiver. This problem is more severe where the characteristics of each available link are different. This causes the receiver to send duplicate acknowledgement and this may induce the sender to infer data loss. This can degrade MPTCP performance because re-ordering is interpreted as sign of congestion. In this paper, we proposed an algorithm that predicts the data segment to be transmitted for a given subflow based on round-trip-time and present congestion state of the subflow. We implemented our proposed algorithm on ns-3 and noticed improvement over simple MPTCP.